2007
DOI: 10.1038/nsmb1332
|View full text |Cite
|
Sign up to set email alerts
|

A YY1–INO80 complex regulates genomic stability through homologous recombination–based repair

Abstract: DNA damage repair is crucial for the maintenance of genome integrity and cancer suppression. We found that loss of the mouse transcription factor YY1 resulted in polyploidy and chromatid aberrations, which are signatures of defects in homologous recombination. Further biochemical analyses identified a YY1 complex comprising components of the evolutionarily conserved INO80 chromatin-remodeling complex. Notably, RNA interference-mediated knockdown of YY1 and INO80 increased cellular sensitivity toward DNA-damagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
224
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(239 citation statements)
references
References 47 publications
15
224
0
Order By: Relevance
“…IR-and UV-induced DNA damages persist in mIno80 ∆/∆ MEFs, suggesting that mIno80 is required for their efficient repair (Figure 3). In addition, we found that mIno80 is required for the generation of ssDNA to mediate HDR at sites of DSBs (Figure 4), in agreement with previous results showing that siRNA-mediated depletion of hIno80 impairs HDR [20,23].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…IR-and UV-induced DNA damages persist in mIno80 ∆/∆ MEFs, suggesting that mIno80 is required for their efficient repair (Figure 3). In addition, we found that mIno80 is required for the generation of ssDNA to mediate HDR at sites of DSBs (Figure 4), in agreement with previous results showing that siRNA-mediated depletion of hIno80 impairs HDR [20,23].…”
Section: Discussionsupporting
confidence: 80%
“…As mIno80 promotes DNA repair and represses genome instability, we postulate that the mIno80 complex also plays a role in tumor prevention. This notion is supported by the observation that hIno80 and its associated protein YY-1 are required to maintain genome stability by promoting proper chromosome segregation [20,22]. We found that deletion of mIno80 severely compromised the tumorigenic potential of transformed mouse cell lines by reducing cellular proliferative capacity and the ability to form soft agar colonies in culture ( Figure 6).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…At the molecular level, it has been demonstrated that regulation of nucleosome deposition is essential for transcriptional activation or repression, 28 -30 DNA replication, 31,32 DNA damage repair, 4,33,34 and cell cycle progression. [35][36][37] Chromatin remodeling factors that control DNA winding/unwinding cycles are therefore believed to be involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast INO80 and SWR1 chromatin remodeling complexes interact with γ-H2A and facilitate DSB repair (van Attikum et al, 2007;Park et al, 2009). Wu and colleagues showed that knockdown models of human INO80, or of its binding partner YY1, increased cellular sensitivity toward DNAdamaging agents, and in their study they highlighted the essentiality of both INO80 and YY1 for HR repair (Wu, S. et al, 2007). However, a recent report indicated that H2A phosphorylation is dispensable for recruitment of the chromatin remodelers INO80 and SNF6 (a component of SWI/SNF) to DSB sites in yeast (Bennett et al, 2013), suggesting that the interaction with γ-H2AX may not be essential for directing the accumulation of histone remodelers at DSB damage sites.…”
Section: Introductionmentioning
confidence: 99%